Vulnerability to sea-level rise of the coast of the Río Negro province - Kokot, R.R. (2004)
According to the global predictions by the International Panel of Climate Change (IPCC), the sea-level rise due to ocean thermal expansion and glacier mass loss will average 0.09 - 0.88 m between 1990 and 2100, with a trend toward an increasing rise rate. Potential impacts of this increasing rise rate relate to changes in the coastal area, including floods, increased coastal retreat, and saline intrusion in the coastal acquiferous and estuaries. In order to achieve an appropriate coastal management scheme in the Province of Río Negro, the area was divided into zones to show information of the level of hazard on a simple map. To identify areas of geological hazard related to permanent and/ or episodic floods, a database was prepared. The threatened or in-danger areas were identified by means of coastal vulnerability indices, also called susceptibility indices, which were calculated by means of an algorithm that relates different variables obtained from coastal geology, and oceanographic and climatological information. This index is defined by seven variables and can be used to identify areas in risk of erosion or permanent/temporary flood. The most vulnerable areas to sea level rise are Balneario El Salado (Playas Doradas), San Antonio Oeste - San Antonio Este, Caleta de los Loros, and the Río Negro mouth. By contrast, vulnerability of the coastal area located to the south of Punta Pórfido is low. © 2004 Asociación Geológica Argentina.